Accessible and Inclusive Public Space: The Regeneration of Waterfront in Informal Areas. Issue 4 (2nd October 2018) - Attia, Sahar; Ibrahim, Asmaa Abdel Aty M.
Abstract : Public open spaces play an important role in achieving equity and inclusion in cities. They are vital elements that shape the urban life and public realm in communities. This paper deals with waterfronts as key spaces in the urban, social, and economic structure of the city, with reference to informal areas where accessibility poses a severe challenge. The paper discusses the interactions between water front uses, potential interventions and the local community's aspirations, while tackling land properties, and participation issues during the decision-making process for regenerating inclusive public spaces. Within this context, the authors present, debate, and analyze the case of Al Warrak Cornish project in the Northern Sector of Giza Governorate in Egypt. They discuss three main aspects in water frontage urban development including: water front as an accessible public space, regeneration as a process, and participation as a tool. This is emphasized through the application of an international policy, namely the three – legged approach that was adopted by the ASUD program in UN Habitat since 2013 (Achieving Sustainable Urban Development) including: Design, regulations, and finance to support developing contexts, aiming at regenerating the waterfront urban area, with the presence of informal urbanization, through the methodology of collaborative and participatory planning. The findings of this research present a methodological decision-making approach for the formalization of the local spatial development framework for waterfronts in informal areas with a focus on the participatory approach. This approach aims at achieving sustainability, and maximizing the economic valorization resulting from the regeneration of informal water frontage areas, balanced with the existing and neighboring community socioeconomic needs. It further highlights the process of reaching common objectives among all stakeholders, especially if they are from different social strata. The paper concludes that this emblematic project possesses significant implications regarding issues of spatial justice, combining conventional road infrastructure with urban regeneration and community energizing as critical aspects of mediating and articulating success in such contexts.